The effect of strength training interventions on people with congenital heart disease: a systematic review - Alan R Barker; Craig A Williams; Kunyu Hao; Curtis Adrian Wadey (Open Heart)
Aim To assess the effectiveness and safety of strength training (ST) interventions in people with congenital heart disease (ConHD).Methods Participants included people of all ages diagnosed with all complexity of ConHD. Interventions included strength training or inspiratory muscle training (IMT) which were delivered in whole or as part of a more holistic programme. Included studies were randomised controlled trials, non-randomised controlled trials and cohort studies. A comprehensive literature search using five databases until June 2023 was conducted. Two authors independently screened all the identified studies and assessed the risk of bias. Due to the paucity of studies and significant differences in study design, albatross plots were produced, and synthesis without meta-analyses was used to assist in the interpretation of results.Results A total of 26 studies were included with a total of 659 participants (53% female). Three of five studies demonstrated that ST significantly improves muscle strength. The albatross plots (20 studies) compared peak oxygen consumption (peak V̇O2) of ST alone, combined training and IMT and showed that 16 studies observed an improvement with a standardised mean difference between 0.10 and 0.50. Combined training was more effective than ST alone and IMT for peak V̇O2, and ST alone was second. The results showed high heterogeneity. Three studies (one ST alone and two combined training) reported a total of five adverse events, but none reported serious adverse events or fatalities.Conclusion This systematic review indicates a moderate improvement in muscle strength by ST alone, with a small improvement in peak V̇O2 in people with ConHD. Although the outcomes are positive, there is still insufficient evidence to establish the clinical significance of ST.